Interchangeability and specificity of components from the quorum-sensing regulatory systems of Vibrio fischeri and Pseudomonas aeruginosa. - Gray, K M (1994)
Autoinduction is a conserved mechanism of cell density-dependent gene regulation that occurs in a variety of gram-negative bacteria. Autoinducible luminescence in Vibrio fischeri requires a transcriptional activator, LuxR, while a LuxR homolog, LasR, activates elastase expression in Pseudomonas aeruginosa. Both LuxR and LasR require specific signal molecules, called autoinducers, for activity. We show here the activation in Escherichia coli of the V. fischeri luminescence (lux) operon by LasR and of the P. aeruginosa elastase gene (lasB) by LuxR when each is in the presence of its cognate autoinducer. Neither LuxR nor LasR showed appreciable activity with the heterologous V. fischeri or P. aeruginosa autoinducer. This supports the view that there is a direct interaction of each transcriptional activator with its proper autoinducer and suggests that there are conserved, autoinduction-related elements within the promoter regions of these genes.